Inovasi : Sebuah pengantar - Mulyono, Fransisca (Business Administration Study Program - Universitas Katolik Parahyangan, 2008)
Most world executives of major industries stated that innovation is one of their three top strategies. Even though this strategy costly, but higher return usually goes satisfactorily. This paper describes the benefit, barriers, consequences of the innovation strategy to disseminate the importance of this strategy for the stakeholder industry, especially in this globalization era. Keywords: invention, innovation, Oslo Manual, Innovation adoption, Innovation diffusion